Pengembangan Sistem Informasi Survei Indeks Kepuasan Masyarakat Berbasis Web di Kantor Kecamatan Bone Kabupaten Bone Bolango - Tumbali, Fratiwi Is.; Katili, Muhammad Rifai; Abdillah, Tajuddin (Diffusion: Journal of Systems and Information Technology, 2024)
The Bone sub-district government conducted a community satisfaction index survey to evaluate public services. However, there are several problems such as; the survey is conducted ahead of data collection from the district, questionnaire answers can be seen directly by the service provider, the process of collecting and processing data is still time-consuming and costly, and there is a lack of technological support. The research aims to increase the value of community services in Bone sub-district through the development of a web-based community satisfaction index survey, for better effectiveness and efficiency. The system development method used is the Agile method. To ensure the use of the system on the user side, System Usability Scale (SUS) testing of the developed system is used. The results of this study indicate that the Community satisfaction index survey information system can support the sub-district in the survey process, management, and data analysis in real time, facilitate the sub-district in printing survey reports, and present survey results in the form of diagrams to facilitate the sub-district in monitoring the results of the Community satisfaction index. An efficient community satisfaction index survey information system. Based on the results of the System Usability Scale (SUS) test, this system has a high level of usability with an average score of 86 (grade A) meeting government needs, and is effective in collecting community satisfaction data.